Smeaton Roman temporary camp (Scottish Historical and Archaeological Internet Reports, 2010)
Prior to investigation the camp had been recorded only as cropmarks on aerial photographs. The road corridor made a substantial transect through the camp available for study. Evidence of prehistoric, Roman, early historic, post-medieval and modern activity was recovered. A discussion of how the camp was interpreted prior to the work and the excavation strategy is followed by archaeological description of the western perimeter camp ditch, the eastern perimeter ditch, 'field ovens', other pits, a linear feature, cultivation furrows and land drains. A sherd of samian is the only artefact of definitive Roman date. There are specialist reports on the samian, prehistoric pottery, lithics, a sculptural fragment, a shale bangle, a decorated cast bronze fragment, wood charcoal and archaeobotanical remains. Six radiocarbon dates were obtained and these are discussed in some detail. The chapter concludes with a discussion of construction methods, date and associations of the Roman camp.